Gasdermin D Mediates Inflammation-Induced Defects in Reverse Cholesterol Transport and Promotes Atherosclerosis - Opoku, Emmanuel; Traughber, Cynthia Alicia; Zhang, David; Iacano, Amanda J.; Khan, Mariam; Han, Juying; Smith, Jonathan D.; Gulshan, Kailash (Frontiers in Cell and Developmental Biology, 2021)
Activation of inflammasomes, such as Nlrp3 and AIM2, can exacerbate atherosclerosis in mice and humans. Gasdermin D (GsdmD) serves as a final executor of inflammasome activity, by generating membrane pores for the release of mature Interleukin-1beta (IL-1β). Inflammation dampens reverse cholesterol transport (RCT) and promotes atherogenesis, while anti-IL-1β antibodies were shown to reduce cardiovascular disease in humans. Though Nlrp3/AIM2 and IL-1β nexus is an emerging atherogenic pathway, the direct role of GsdmD in atherosclerosis is not yet fully clear. Here, we used in vivo Nlrp3 inflammasome activation to show that the GsdmD–/– mice release ∼80% less IL-1β vs. Wild type (WT) mice. The GsdmD–/– macrophages were more resistant to Nlrp3 inflammasome mediated reduction in cholesterol efflux, showing ∼26% decrease vs. ∼60% reduction in WT macrophages. GsdmD expression in macrophages exacerbated foam cell formation in an IL-1β dependent fashion. The GsdmD–/– mice were resistant to Nlrp3 inflammasome mediated defect in RCT, with ∼32% reduction in plasma RCT vs. ∼57% reduction in WT mice, ∼17% reduction in RCT to liver vs. 42% in WT mice, and ∼37% decrease in RCT to feces vs. ∼61% in WT mice. The LDLr antisense oligonucleotides (ASO) induced hyperlipidemic mouse model showed the role of GsdmD in promoting atherosclerosis. The GsdmD–/– mice exhibit ∼42% decreased atherosclerotic lesion area in females and ∼33% decreased lesion area in males vs. WT mice. The atherosclerotic plaque-bearing sections stained positive for the cleaved N-terminal fragment of GsdmD, indicating cleavage of GsdmD in atherosclerotic plaques. Our data show that GsdmD mediates inflammation-induced defects in RCT and promotes atherosclerosis.